A polysomnographic study of daytime sleepiness in myotonic dystrophy type 1. Issue 6 (11th February 2009) - Laberge, L; Bégin, P; Dauvilliers, Y; Beaudry, M; Laforte, M; Jean, S; Mathieu, J
Abstract : Objectives: To assess contributors to excessive daytime sleepiness (EDS) in myotonic dystrophy type 1 (DM1), to characterise subjects with sleep-onset REM periods (SOREMPs), and to verify whether self-reported instruments and respiratory function tests can predict multiple sleep latency test (MSLT) and sleep-disordered breathing. Methods: A sample of 43 DM1 patients without selection bias underwent polysomnography (PSG) for two consecutive nights and MSLT, completed a sleep diary and Epworth Sleepiness Scale (ESS), and were assessed for respiratory function and narcolepsy symptoms. Results: ESS scores (ES) ⩾11 and MSLT mean sleep latency (MSL) ⩽8 min were found in 21 (50.0%) and 19 (44.2%) subjects, and either in 30 (69.8%) subjects. ES did not relate to MSL. Subjects with subjective sleepiness (ES⩾11) reported more cataplexy-like and sleep paralysis symptoms, longer habitual sleep times, and higher sleep efficiency and REM sleep per cent than those without. Subjects with objective sleepiness (MSL⩽8 min) had a higher stage 4 sleep per cent. Subjects with ⩾2 SOREMPs (25.6%) showed higher muscular impairment, lower MSL, higher ES, and more cataplexy-like symptoms than those with ⩽1 SOREMP. Apnoea-hypopnoea index (AHI) ⩾5, predominantly obstructive, was found in 37 (86.0%) subjects, and AHI >30 in 12 (27.9%). Neither subjective nor objective sleepiness could be explained by AHI, nor satisfactorily predicted by daytime respiratory abnormalities. Conclusions: DM1 entails frequent EDS but with different phenotypes and distinct mechanisms involved. The high prevalence of daytime sleepiness and severe sleep apnoeas found in this study supports the routine use of clinical sleep interviews, PSG and MSLT in DM1, and emphasises the need for more randomised trials of psychostimulants.